The Influence of Teaching Skills and Effective Communication on The Professional Competencies of Physical Education Teachers - Widyaningsih, Heni; Asmawi, Moch.; Tangkudung, James (Journal of Education, Health and Sport, 2020)
In Indonesia, teacher should have four competencies, namely pedagogic competence, social competence, personality competency and professional competence. This study aims to determine the influence of teaching skills and effective communication on performance of physical education teachers. This study uses associative quantitative method by using multiple correlation models. The population and sample are physical education teachers who took the program of Education and Training of Professional Teacher called PLPG at Universitas Negeri Jakarta. The results of this study are (1) there is significant influence between teaching skills to performance of physical education teachers as professional competencies, (2) there is significant influence between effective communication to performance of physical education teachers as professional competencies and (3) there is significant influence between teaching skill and effective communication to performance of physical education teachers as professional competencies.